Degradation kinetics of anthocyanin extracted from roselle calyces (Hibiscus sabdariffa) - Maripillai Munusamy Pragalyaashree, Deivanayagame Tiroutchelvame, Siddant Sashikumar (Journal of Applied Pharmaceutical Science, 2018)
Roselle calyces (Hibiscus sabdariffa) pigment contains an inexpensive source of anthocyanins, which is used as a natural colorant in food preparation instead of artificial colors. Hence, a study was carried out to extract anthocyanin from roselle calyces using acidified ethanol. The pigment stability during storage under different temperature conditions was also investigated. Kinetics study of the roselle extract was conducted to find out the degradation rate. It was concluded that the pigment stored in an amber bottle under refrigerated conditions showed least degradation rate with a k value of 0.0017, followed by the pigment stored in a transparent bottle under refrigerated conditions with a k value of 0.0025. The highest degradation rate was found when the pigment was stored in the transparent bottle at 40°C under light with a k value of 0.0055. The half-life periods of the pigment extract stored in amber bottle and transparent bottle under refrigerated condition (10°C), dark and light condition at 40°C were 407.73, 277.25, 223.59, 138.62, 147.47, and 126.02 days, respectively. From the results of the experiments, it was found that the roselle calyces (Hibiscus sabdariffa) is a potential source of natural anthocyanin which can be used as a natural colorant in various food formulations.
Keywords: Hibiscus sabdariffa (Roselle), anthocyanin, optimization, calyx, ethanol extraction, kinetics study, half-life period.